Sentence contexts and cloze probabilities for Brazilian Portuguese children and adolescents - Rossi, Natalia Freitas [UNESP]; Fernandes, Catarina; Moreira, Célia Sofia; Giacheti, Célia Maria [UNESP]; Sichieri, Bianca Bortolai [UNESP]; Pinheiro, Ana Patrícia; Sampaio, Adriana (Public Library of Science (PLoS), 2020)
PURPOSE: In this study we investigated a set of 100 sentence contexts and their cloze probabilities to develop a database of linguistic stimuli for Brazilian Portuguese children and adolescents. The study also examined age-related changes on cloze probabilities, and specified the predictor effects of age and cloze probabilities on idiosyncratic responses and errors (semantic, syntactic, and other errors). Finally, the study also aimed to shed light on cultural effects on word generation by comparing Brazilian and Portuguese sentence databases. METHOD: 361 typically developing monolingual Brazilian speakers, with ages ranging from 7 to 18 years, participated in the study. The cloze task was composed by 100 sentence contexts, grounded on the European Portuguese database. Responses were classified as valid (correct) or invalid (semantic, syntactic, and other-type errors). Statistical analyses were based on mixed-effects logistic models. RESULTS: Sixty-three sentences met criteria for high cloze probabilities, 30 for medium cloze, and 7 for low cloze. Age was a significant predictor of idiosyncratic responses, semantic and syntactic errors: older participants were less likely to produce idiosyncratic responses, as well as semantic and syntactic errors. Cloze probability values were concordant in the Brazilian and Portuguese databases for 31 out of 49 (83.7%) high-cloze sentences and for 7 low-cloze sentences. CONCLUSION: In this study we have provided a database with cloze probability values for a set of 100 sentence-final word contexts for Brazilian Portuguese children and adolescents. Results showed that both age and sentence contextual level predicted sentence final word completion. Older participants were more likely to choose more consistently the same final word, with the contextual level of a given sentence also contributing to the final word selection. Age should be controlled for in future studies probing semantic processing with this set of sentences.